Colombian Truth Commission: Knowledge, perception, efficacy, and associated emotions (2022)
The Truth Commission in Colombia was established based on the transitional justice model. Its function is to serve as a measure of recognition of the violent events during the armed conflict, which has left more than nine million victims. In this scenario, a descriptive correlational study (N=1166) was conducted with a sample of 22 provinces of the country to evaluate the knowledge, approval, and perceived effectiveness of the first years of the Commission from psychosocial aspects: victimization, collective emotions, reconciliation, collective memory. 58% were direct victims. The results indicate high levels of approval and disposition to participate in the Commission’s activities, as well as some skepticism about its usefulness and low confidence in the official apologies of the groups in conflict. A high index of positive emotions related to the commission and low trust in government institutions is also found. The findings of this study coincide with previous experiences of truth commissions in Latin America and open the debate on the specificities of the Colombian context in the search for peace and the implications of the commission’s work in the reparation process. © 2022 Pontificia Universidad Catolica del Peru. All rights reserved.